Skin Friction Of Excavated Piles In Weathered Granite - Synopsis - K. K. S. Ho (Deep Foundations Institute, 1996)
In Hong Kong the design of excavated piles in weathered granite has conventionally been based on a rule-of-thumb which relates the allowable base bearing capacity to the SPT N value, with no allowance for skin friction. This rule-of-thumb has been shown to generally lead to conservative designs. To improve the overall understanding of load-transfer mechanism of excavated piles in weathered granite, instrumented pile load tests have been conducted. This paper summarises a selection of instrumented pile load test data in Hong Kong and the observations made of the results, which indicate that there was considerable scatter in the back-calculated skin friction values. However, the mobilized skin friction was shown to be significant which can lead to substantial savings in design.